Effects of spinetoram and glyphosate on physiological biomarkers and gut microbes in Bombus terrestris - Tang, Qi-He; Li, Wan-Li; Wang, Jie-Ping; Li, Xi-Jie; Li, Dan; Cao, Zhe; Huang, Qi; Li, Jia-Li; Zhang, Jun; Wang, Zheng-Wei; Guo, Jun; Li, Ji-Lian (Frontiers in Physiology, 2023)
The sublethal effects of pesticide poisoning will have significant negative impacts on the foraging and learning of bees and bumblebees, so it has received widespread attention. However, little is known about the physiological effects of sublethal spinetoram and glyphosate exposure on bumblebees. We continuously exposed Bombus terrestris to sublethal (2.5 mg/L) spinetoram or glyphosate under controlled conditions for 10 days. The superoxide dismutase, glutathione-S-transferase, carboxylesterase, prophenoloxidase, α-amylase and protease activities, and changes in gut microbes were measured to understand the effects of sublethal pesticide exposure on the physiology and gut microbes of bumblebees. Sublethal pesticide exposure to significantly increased superoxide dismutase activity and significantly decreased gut α-amylase activity in bumblebees but had no significant effect on glutathione-S-transferase, carboxylesterase or gut protease activities. In addition, glyphosate increased the activity of prophenoloxidase. Interestingly, we observed that neither of the two pesticides had a significant effect on dominant gut bacteria, but glyphosate significantly altered the structure of the dominant gut fungal community, and reduced the relative abundance of Zygosaccharomyces associated with fat accumulation. These results suggest that sublethal spinetoram and glyphosate do not significantly affect the detoxification system of bumblebees, but may affect bumblebee health by inhibiting energy acquisition. Our results provide information on the sublethal effects of exposure to low concentrations of glyphosate and spinetoram on bumblebees in terms of physiology and gut microbes.